Laminin and Environmental Cues Act in the Inhibition of the Neuronal Differentiation of Enteric Glia in vitro - Veríssimo, Carla Pires; Carvalho, Juliana da Silva; Silva, Fábio Jorge Moreira da; Campanati, Loraine; Moura-Neto, Vivaldo; Coelho-Aguiar, Juliana de Mattos (Frontiers in Neuroscience, 2019)
The enteric glia, a neural crest-derived cell type that composes the Enteric Nervous System, is involved in controlling gut functions, including motility, gut permeability, and neuronal communication. Moreover this glial cell could to give rise to new neurons. It is believed that enteric neurons are generated up to 21 days postnatally; however, adult gut cells with glial characteristics can give rise to new enteric neurons under certain conditions. The factors that activate this capability of enteric glia to differentiate into neurons remain unknown. Here, we followed the progress of this neuronal differentiation and investigated this ability by challenging enteric glial cells with different culture conditions. We found that, in vitro, enteric glial cells from the gut of adult and neonate mice have a high capability to differentiate into neurons, progressing in acquiring neuronal markers and undergoing morphological changes. In a co-culture system with 3T3 fibroblasts, the number of glial cells entering neurogenesis decreased after 7 days. The effect of 3T3-conditioned medium on adult cells was not significant, and fewer enteric glial cells from neonate mice began the neurogenic process in this medium. Laminin, an extracellular matrix protein that is highly expressed by the niche of the enteric ganglia, seemed to have a large role in inhibiting the differentiation of enteric glia, at least in cells from the adult gut. Our results suggest that, in an in-vitro approach that provides conditions more similar to those of enteric glial cells in vivo, these cells could, to some extent, retain their morphology and marker expression, with their neurogenic potential inhibited. Importantly, laminin seemed to inhibit differentiation of adult enteric glial cells. It is possible that the neurogenic differentiation of enteric glia is related to severe changes in the microenvironment, leading to disruption of the basement membrane. In summary, our data indicated that the interaction between the enteric glial cells and their microenvironment molecules significantly affects the control of their behavior and functions.